Is genetic diversity congruent with morphological diversity across the distributional range of the Melampyrum subalpinum group (Orobanchaceae)? - Chlumský, Jan (Jihočeská univerzita, 2016)
Allozymes were used to assess the genetic structure of 27 populations of Melampyrum subalpinum group and an artificial pollination experiment was carried out to examine the possibility of autogamy. Genetic variation was generally congruent with the known morphological variation of the group. The results corresponded with the central-marginal concept. Allelic enrichment due to hybridization with M. nemorosum was observed in some Austrian populations. Czech and Slovak populations do not differ from Austrian populations. The high inbreeding coefficient and the pollination experiment do not contradict the possibility of autogamy.
Is genetic diversity congruent with morphological diversity across the distributional range of the Melampyrum subalpinum group (Orobanchaceae)?
Keywords: allozymes; population genetics; hemiparasites; marginal populations; allozymes; population genetics; hemiparasites; marginal populations